Towards Efficient, Secure, and Fine-Grained Access Control System in MSNs with Flexible Revocations. (27th January 2015) - Sun, Shi-Feng; Lyu, Chen; Gu, Dawu; Zhang, Yuanyuan; Ren, Yanli
Abstract : With the pervasiveness of mobile communications, MSNs have become a promising networking paradigm for users to share contents with others through mobile devices. This convenience comes at the cost of some serious security and privacy issues. In this work, we propose a novel privacy-preserving scheme for MSNs, which can efficiently solve some of the most serious security and privacy issues such as data confidentiality, fine-grained access control, and flexible revocation. In particular, we leverage the attribute based encryption technique to realize fine-grained access control over encrypted data. Moreover, we enhance this technique and design a flexible and fine-grained revocation mechanism which enables not only efficient user revocation but also efficient attribute revocation. As we show, our system can achieve both forward secrecy and backward secrecy using such mechanism. We compare our scheme with other related works and show that not only most of the previous works suffer from larger size of encrypted data but also their decryption time grows linearly with the complexity of access policies. In comparison, our scheme achieves higher efficiency and smaller computation time while consuming lesser storage space. We provide extensive analysis and performance evaluation to demonstrate the security, scalability, and efficiency of our proposed framework.